Being human. (July 2015) - Phillips, Anthony
What it is to be human is best understood from the Hebrew concept of the nephesh, best translated as 'personality'. This controls both thoughts and actions, and even expresses itself through personal property. It is though only by the exercise of a proper selfishness that the nephesh is able to achieve self-fulfilment. This cannot be done either in isolation from others, or without space to listen and to look, or by ignoring one's failures. In the end everyone's vocation is to secure both for themselves and others their essential humanity by being their own unique nephesh.